The Marseille caper - Mayle, Peter (Mayle, Peter. Sam Levitt mysteries., 2012)
Unable to resist an exciting job offer in Marseille, Sam Levitt and his girlfriend Elena find their happy return to the region's coastal sunshine and delectable cuisine challenged by an increasingly violent competition for waterfront property.